Chronic dislocations of the shoulder [Kronik omuz çikiklari.] - (:unkn) unknown (My University, 2005)
Diagnosis and management of chronic dislocations of the glenohumeral joint remain challenging. These dislocations usually occur in debilitated patients with a poor bone quality and they often have a decreased rehabilitation potential. Treatment can only be successful with early recognition of the condition, careful patient selection, and implementation of appropriate surgical techniques. This article reviews current information on clinical evaluation, preoperative radiologic investigations, and treatment strategies in patients with chronic dislocations of the glenohumeral joint and associated articular surface defects.